The Effectiveness of Parent Education in Discharge-Symptom Management (PED-SM) on Parental Readiness to Care for Children with Cancer - Ruriwinta, Ruriwinta; Perdani, Agni Laili; Calisanie, Nyayu Nina; P, Nyimas Heny; Apriliawati, Anita (Jurnal Pendidikan Keperawatan Indonesia, 2024)
Introduction: Cancer in children is a life-threatening disease that has been steadily increasing over the past few decades. Parents are concerned about how to appropriately care for children due to the physical symptoms experienced by children with cancer. Objective: The purpose of this study was to determine the effect of Parent Education in Discharge Symptom Management (PED-SM) on parental readiness to care for children with cancer. Methods: This research utilized a quasi-experimental design with intervention and control groups, measured using a pre-post test design. Respondents in this study were parents of children aged 3 to 12 years newly diagnosed with cancer. A convenience sampling method was employed. The instrument used in this study was the I-PCS (Preparedness of Caregiving Scale-Indonesian) with a Cronbach's alpha of 0.73-0.78, where a Pearson's r 0.320 indicates validity. Results: A total of 58 respondents agreed to participate in this study. The mean age of parents was higher in the control group (39.48), while the mean age of children was lower (7.38). More than half of the children were boys with ALL/AML cancer types. Parents mostly worked full time, had education up to junior or senior high school, and had a monthly income of 4.9 million. There was a statistically significant difference after the intervention in both groups, with a p-value 0.005. However, the mean score after intervention (45.76 ± 5.81) was higher compared to the control group (32.34 ± 4.41). Employment showed a significant contribution of 6.52 to parental readiness among parents of children with cancer (β: 1.87, 95% CI: 1.29 – 32.97, p-value: 0.02). The intervention of PED-SM can be implemented by pediatric nurses in cancer units as one of educational tool aimed at reducing readmissions and enhancing the quality of life for children. Conclusion: The PED-SM module can serve as a reference for educating families of children newly diagnosed with cancer.